ANALYSIS OF THE INFLUENCE OF LOCATION, INTEREST RATE, SERVICE, AND PROMOTION ON CUSTOMER DECISIONS IN LOAN MAKING (Studies at PT. BPR BKK Tegal City) - Fidyah Yuli Ernawati; Arini Novandalina; Rokhmad Budiyono; Herwinda Nur Indah Sari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Banks are intermediary institutions that collect funds and distribute them in the form of placements in earning assets. One of the productive assets that contributes the most to bank income is credit. Based on its use, credit is divided into three, namely: working capital credit, investment credit, and consumption credit. Working capital credit is a loan that is given to finance the working capital of a business. The purpose of this study was to determine the effect of location, interest rates, services, and promotions on credit decisions at PT. BPR BKK Tegal City. The population in this study were all credit customers of PT. BPR BKK Tegal City in August 2021 as many as 1087 customers. So that the obtained sample amounted to 100 respondents. The variable in this study is the independent variable (X) consisting of location, interest rates, services, promotions, and the dependent variable (Y) is credit decision making. Data collection method is done by distributing questionnaires. The method of analysis is the Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Testing. From the results of the study showed that the location variable did not have a significant effect on credit decision making with a significant value of 0.852 > 0.05. The interest rate has a significant influence on credit decision making with a significant value of 0.010 < 0.05. Service does not have a significant influence on credit decision making with a significant value of 0.225 > 0.05. Promotion does not have a significant effect on credit decision making with a significant value of 0.180 > 0.05. So that the statistical calculation shows that partially the interest rate variable has a significant influence on credit making decisions. Meanwhile, location, service and promotion do not have a significant influence on credit decision making. Location has no influence on credit decisions, a strategic, safe and comfortable location is something that must be considered. Interest rates have an influence on credit decision making, by providing the right interest rate it is expected to increase customer interest in taking credit. The service has no influence on credit decisions, friendly, courteous and satisfying service can make customers feel at home and want to return to doing transactions at the bank. Promotion has no influence on credit decision making. This is expected to contribute more to the increase in the number of credit customers at PT. BPR BKK Tegal City.